Aves, Charadriiformes, Scolopacidae, Limosa haemastica (Linnaeus, 1758): first record from South Shetland Islands and Antarctic Peninsula, Antarctica - Juares, Mariana Alejandra (2010)
We report herein the southernmost record of the Hudsonian Godwit (Limosa haemastica), at two localities in the Antarctic: Esperanza/Hope Bay (January 2005) and 25 de Mayo/King George Island (October 2008). On both occasions a pair of specimens with winter plumage was observed.